2018
DOI: 10.3233/aac-170031
|View full text |Cite
|
Sign up to set email alerts
|

Abstract solvers for Dung’s argumentation frameworks

Abstract: TU Wien, Austria E-mails: linsbich@dbai.tuwien.ac.at, wallner@dbai.tuwien.ac.at, woltran@dbai.tuwien.ac.at Abstract. Abstract solvers are a quite recent method to uniformly describe algorithms in a rigorous formal way via graphs. Compared to traditional methods like pseudo-code descriptions, abstract solvers have several advantages. In particular, they provide a uniform formal representation that allows for precise comparisons of different algorithms. Recently, this new methodology has proven successful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As far as the application of abstract solvers methodology outside ASP is concerned, the first application has been already mentioned and is related to the seminal paper (Nieuwenhuis et al 2006), where SMT problems with certain logics via a lazy approach (Sebastiani 2007) are considered. Then, abstract solvers have been presented for the satisfiability of Quantified Boolean Formulas by Brochenin and Maratea (2015b), and for solving certain reasoning taks in Abstract Argumentation under preferred semantics (Brochenin et al 2018). Finally, in another number of papers, starting from a developed concept of modularity in answer set solving (Lierler and Truszczynski 2013), abstract modeling of solvers for multi-logic systems are presented (Lierler and Truszczynski 2014;Lierler and Truszczynski 2015;Lierler and Truszczynski 2016).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the application of abstract solvers methodology outside ASP is concerned, the first application has been already mentioned and is related to the seminal paper (Nieuwenhuis et al 2006), where SMT problems with certain logics via a lazy approach (Sebastiani 2007) are considered. Then, abstract solvers have been presented for the satisfiability of Quantified Boolean Formulas by Brochenin and Maratea (2015b), and for solving certain reasoning taks in Abstract Argumentation under preferred semantics (Brochenin et al 2018). Finally, in another number of papers, starting from a developed concept of modularity in answer set solving (Lierler and Truszczynski 2013), abstract modeling of solvers for multi-logic systems are presented (Lierler and Truszczynski 2014;Lierler and Truszczynski 2015;Lierler and Truszczynski 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Another added, general, value of our paper is in its practical part, i.e., an implementation of new solutions designed through abstract solvers. In fact, while nowadays abstract solvers methodology has been widely used, often in the mentioned papers the presented results have rarely led to implementations, with the exception of (Nieuwenhuis et al 2006), where the related BARCE-LOGIC implementation won the SMT Competition 2005 on same logics, and (Lierler 2011), where a proposed combination of SMODELS and CMODELS techniques has been implemented in the solver SUP, that reached positive results at the ASP Competition 2011 and, more recently, (Brochenin et al 2018), where the new designed solution, obtained as a modification of the CEGARTIX solver, performed often better than the basic CERGATIX solver on preferred semantics, that was among the best solvers in the first ICCMA competition.…”
Section: Related Workmentioning
confidence: 99%
“…A set of arguments and the relationships between them can be represented as a directed graph (referred to as an argumentation framework) to which one of a number of semantics can be applied to determine which arguments it is coherent to accept [12]. While progress has been made in the development of argumentation-based technologies (e.g., argument solvers [5] and real-world applications [18]) realistic evaluations of such technologies is difficult, due to the shortage of repositories of argumentation frameworks that are representative of real-world domains [10]; typically, argument technologies are evaluated on randomly generated frameworks, with little understanding of how the structure of such frameworks impacts on performance. It has been shown that structural differences in argumentation frameworks can affect the performance of argumentation-based technologies, such as dialogue systems [3] and argument solvers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Existing works in the abstract argumentation field [18,19] either focus on algorithm selection for enumerating preferred extensions, with a very small number of solvers and of instances; or on theoretical complementariness of algorithms.…”
mentioning
confidence: 99%